Varieties of Participation in Public Services: The Who, When, and What of Coproduction. (30th March 2017) - Nabatchi, Tina; Sancino, Alessandro; Sicilia, Mariafrancesca
Abstract: Despite an international resurgence of interest in coproduction, confusion about the concept remains. This article attempts to make sense of the disparate literature and clarify the concept of coproduction in public administration. Based on some definitional distinctions and considerations about who is involved in coproduction, when in the service cycle it occurs, and what is generated in the process, the article offers and develops a typology of coproduction that includes three levels (individual, group, collective) and four phases (commissioning, design, delivery, assessment). The levels, phases, and typology as a whole are illustrated with several examples. The article concludes with a discussion of implications for research and practice.